Gingival crevicular fluid semaphorin 4D and peptidylarginine deiminase‐2 levels in periodontal health and disease. Issue 9 (13th May 2019) - Veyisoğlu, Gözde; Savran, Levent; Narin, Figen; Yılmaz, Huriye Erbak; Avşar, Candeğer; Sağlam, Mehmet
Abstract: Background: The aim of this study was to compare the levels of semaphorin 4D (SEMA4D), peptidylarginine deiminase 2 (PAD2) and matrix metalloproteinase‐8 (MMP‐8) in gingival crevicular fluid (GCF) in patients with periodontal disease and patients with healthy periodontium and investigate the effects of periodontal treatment on the levels of these molecules. Methods: GCF samples were collected from periodontally healthy controls (C group, n = 20), patients with gingivitis (G group, n = 20), and patients with chronic periodontitis (CP group, n = 20). Sampling sites were also divided into bleeding (BP) and non‐bleeding (NBP) periodontal pocket groups in CP group. Full‐mouth clinical periodontal parameters were also recorded. GCF samplings and clinical records were also repeated at 1 and 3 months after treatment for the CP group. SEMA4D, PAD2, and MMP‐8 levels were determined by enzyme‐linked immunosorbent assay. Results: The GCF SEMA4D, PAD2, and MMP‐8 total amounts were similar in CP and G groups ( P  ˃ 0.05) but significantly greater than the C group ( P  ˂ 0.05). The GCF SEMA4D and PAD2 total amounts in the BP group were significantly greater than the NBP group ( P  ˂ 0.05). GCF MMP‐8 total amounts were similar in BP and NBP groups ( P  ˃ 0.05). The GCF SEMA4D, PAD2, and MMP‐8 total amounts were significantly reduced at first month after treatment ( P  ˂ 0.05). There were positive correlations between GCF total amount of SEMA4D and all clinical parameters ( P  ˂ 0.01) and also between PAD2 and clinical parameters ( P  ˂ 0.05) except clinical attachment level. There was a positive correlation between GCF total amount of SEMA4D and GCF total amount of MMP‐8 ( P  ˂ 0.05). Conclusions: It may be suggested that SEMA4D and PAD2 are related to periodontal disease. Their GCF total amounts may have a diagnostic potential. Additional studies would better clarify their role in periodontal diseases.